2011
DOI: 10.1016/b978-0-12-385895-5.00003-7
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junctions and Chagas Disease

Abstract: Gap junction channels provide intercellular communication between cells. In the heart, these channels coordinate impulse propagation along the conduction system and through the contractile musculature, thereby providing synchronous and optimal cardiac output. As in other arrhythmogenic cardiac diseases, chagasic cardiomyopathy is associated with decreased expression of the gap junction protein connexin43 (Cx43) and its gene. Our studies of cardiac myocytes infected with Trypanosoma cruzi have revealed that syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 51 publications
2
28
0
4
Order By: Relevance
“…31 The reduction of gap junctions in T. cruzi-infected cells and T. cruzi-infected mice has been known since 1992 and has been extensively studied. 55,56 Gap junctions are plaques of intercellular channels composed of 12 connexin (Cx) molecules assembled into connexons. They connect the cytoplasm of adjacent cells, allowing propagation of electrical impulses.…”
Section: Review Implication Of Tgf-β In Cardiac Complications Of Chagmentioning
confidence: 99%
“…31 The reduction of gap junctions in T. cruzi-infected cells and T. cruzi-infected mice has been known since 1992 and has been extensively studied. 55,56 Gap junctions are plaques of intercellular channels composed of 12 connexin (Cx) molecules assembled into connexons. They connect the cytoplasm of adjacent cells, allowing propagation of electrical impulses.…”
Section: Review Implication Of Tgf-β In Cardiac Complications Of Chagmentioning
confidence: 99%
“…We have found that infection with Trypanosoma cruzi , the causative agent of Chagas disease, alters gap junction expression in cultured cells obtained from heart and brain [1214]. In T. cruzi -infected adipose tissue and cultured adipocytes there is upregulation of inflammatory mediators [1518].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that dampening of electrogenesis and bradyarrhythmias is due to the presence of autoantibodies against the second extracellular loop of cardiac M2 acetylcholine receptor and b2 adrenoceptor (26,27). Interestingly, some investigators have reported a decrease in the expression of connexin 43, a gap junction protein, in the infected cardiac myocytes (28). This implies a causal relationship between parasitic infection and cardiac conduction disorders.…”
Section: Discussionmentioning
confidence: 97%